2019
DOI: 10.1080/02827581.2019.1589567
|View full text |Cite
|
Sign up to set email alerts
|

Nearest neighbor imputation of logwood volumes using bi-temporal ALS, multispectral ALS and aerial images

Abstract: We examine the nearest neighbor (NN) imputation of species-specific logwood volumes using airborne laser scanning (ALS) data and aerial images. We compare different remote sensing (RS) data combinations as predictor variables in an area-based prediction of logwood volumes using separate training and validation data. We include multispectral leaf-on ALS data, bi-temporal leaf-off ALS data and aerial images in the analyses. Two response configurations were used in the NN imputations: (1) simultaneous imputation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…To the best of this author's knowledge, only two studies, in addition to this thesis, have applied ABA in the prediction of boreal tree species attributes using M-ALS. Räty et al (2019) found that M-ALS features slightly decreased the prediction errors associated with logwood volumes compared to features calculated from U-ALS data. Dalponte et al (2018) predicted the Shannon diversity index of tree species.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…To the best of this author's knowledge, only two studies, in addition to this thesis, have applied ABA in the prediction of boreal tree species attributes using M-ALS. Räty et al (2019) found that M-ALS features slightly decreased the prediction errors associated with logwood volumes compared to features calculated from U-ALS data. Dalponte et al (2018) predicted the Shannon diversity index of tree species.…”
Section: Discussionmentioning
confidence: 84%
“…The intensities of M-ALS are considered beneficial in the classification of tree species, both using ABA (Dalponte et al 2018;Räty et al 2019) and ITD (Yu et al 2017;Axelsson et al 2018;Budei et al 2018). Although prediction errors or classification accuracies are not directly comparable between ITD and ABA, we can examine whether similar features were important predictors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tree locations were determined using a variant of the triangulation method proposed by Korpela et al (2007). Field measurements are documented in detail in Räty et al (2019). The central 10 × 10 m 2 of every plot was covered with a triangular grid where the distance between points was at least 1 m. Every grid point was used as a center for a simulated circular sampling plot with radius 10 m. If a tree stem covered the center point, it was removed.…”
Section: Field Datamentioning
confidence: 99%